Evaluating Effect of Prophylactic Intravenous Dexamethasone in Post Spinal Shivering: A Single Centre Randomised Controlled Study - Yeoh, Dr Chih Nie; Voon, Dr Billy; Mohamad Mahdi, Datin Dr Siti Nidzwani; Sayed Masri, Dr Syarifah Noor Nazihah; Izaham, Associate Professor Dr Azarinah (IIUM Medical Journal Malaysia, 2021)
Introduction: Shivering is a common side effect of central neuraxial anaesthesia. Intravenous pethidine is commonly used in reducing shivering but has been associated with significant opioid side effects. Dexamethasone as a powerful anti-inflammatory and analgesia agent is postulated to inhibit inflammatory mediators’ release thus inhibiting central thermoregulatory centre, potentially attenuating post spinal shivering. This double-blinded randomised controlled study was to determine the ability of intravenous dexamethasone in decreasing the incidence, severity and the need for treatment for post spinal shivering. Methods: We recruited 72 patients requiring spinal anaesthesia and randomised them to receive either dexamethasone 0.1 mg/kg (up to 8 mg) or normal saline (placebo). We observed their tympanic membrane temperatures, mean arterial pressures and shivering scores at regular intervals up to 2 hours post-spinal or till end of surgery (minimum 30 minutes post spinal). Results: Both groups showed consistent and comparable drop in tympanic membrane temperatures and mean arterial pressures after spinal anaesthesia, except at 15 minutes in which patients of dexamethasone group demonstrated significantly higher temperatures than saline group (p=0.04). There were also significantly less patients in the dexamethasone group reporting incidence of visible shivering as compared to the placebo group (p=0.003). No significant difference was seen in severity of shivering or usage of pethidine. Conclusion: Dexamethasone has the potential to mitigate the reduction in core body temperature, especially at 15 minutes post spinal. It can reduce the incidence of clinically significant visible grade of shivering post spinal.